Prognostic Value of the Cell Cycle Progression Score in Patients with Prostate Cancer: A Systematic Review and Meta-analysis - Sommariva, Silvia; Tarricone, Rosanna; Lazzeri, Massimo; Ricciardi, Walter; Montorsi, Francesco (European urology, 2016)
The process of care for patients with prostate cancer is subject to different degrees of uncertainty. Patients and clinicians could, therefore, greatly benefit from improved prognostic instruments. One emerging tool is the cell cycle progression (CCP) score. This systematic review assesses evidence on the value of the CCP instrument in prostate cancer treatment by reviewing current publications and integrating the results via a meta-analysis. We performed a review of Medline and Embase in April 2014, according to Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA). Unpublished studies were retrieved from the 2013–2014 proceedings of major conferences in the field. Sixteen publications were selected for inclusion. The results show that use of the CCP score is better than existing assessments at elucidating the aggressive potential of prostate cancer in an individual. The pooled hazard ratio for biochemical recurrence per 1-unit increase in the CCP score was 1.88 in a univariate model and 1.63 in a multivariate model. Four studies showed that CCP testing can impact the decisions of physicians regarding treatment, and potentially lead to a decrease in surgical interventions for low-risk patients. This review offers a comprehensive overview of existing evidence on CCP testing, and provides clinicians, patients, and policy makers with a strong summary measure of its prognostic validity and clinical utility. It will be important to develop economic studies to measure the impact of such technology on health care systems. In this paper, we review current evidence related to the cell cycle progression (CCP) score for patients with prostate cancer. We found good evidence suggesting that use of the CCP score improves prognosis, and can be a valuable tool for clinicians in treating patients. The economic benefits are yet to be studied. This systematic review offers a comprehensive overview of the state of the art of existing evidence on cell cycle progression testing with the Prolaris test, and provides clinicians, patients, and policy-makers with a strong summary value for its prognostic validity.